Achievements in the Synthesis of Elemental Silver Nanoparticles with Various Geometric Forms - Mikhailov, Oleg V. (Current Nanoscience, 2019)
Background: The data on the specific synthesis of elemental silver nanoparticles (Ag-NP) having the forms of various geometric bodies (pseudo spherical, prismatic, cubic, trigonal-pyramidal, etc.), obtained by various methods, have been systematized and generalized. Objective: It is noted that the forms and sizes of Ag-NP are greatly dependant on the conditions in which they are formed. Method: Comparison of the data of the characteristics of silver nanoparticles obtained by chemical, physicochemical and biological methods has been made. Results: It has been shown that form and size of produced Ag-NP depend strongly on the such factors as temperature, the concentration of silver(I) containing precursor, pH of the solution, the molar ratio between capping agent and silver(I) containing precursor, reducing agents etc., and, also, on the method used for Ag-NP synthesis (chemical, physicochemical or biological). Conclusion: It has also been noted that biological methods of synthesis of Ag-NP are generally more preferable in comparison with the chemical and physicochemical methods. The review covers mainly publications published in the last 20 years.
Keywords: synthesis